Spanish Civic Engagement: a bridge among civil society, politics and public administration - Serrano, Alejandro Álvarez; Meek, Jack (Revista Científica Foz, 2018)
This paper, recognizing the many ways of civil and institutional cooperation, briefly examines the concept of civic engagement and civil society and applies this understanding to a recent case about an association encouraging participation (Principos) of the civil society in the political sphere in Madrid, Spain.